The gasdermins: a pore-forming protein family expressed in the epidermis - Slaufova, Marta; Karakaya, Tugay; Di Filippo, Michela; Hennig, Paulina; Beer, Hans-Dietmar (Frontiers in Immunology, 2023)
Gasdermins comprise a family of pore-forming proteins, which play critical roles in (auto)inflammatory diseases and cancer. They are expressed as self-inhibited precursor proteins consisting of an aminoterminal cytotoxic effector domain (NT-GSDM) and a carboxyterminal inhibitor domain (GSDM-CT) separated by an unstructured linker region. Proteolytic processing in the linker region liberates NT-GSDM, which translocates to membranes, forms oligomers, and induces membrane permeabilization, which can disturb the cellular equilibrium that can lead to cell death.Gasdermin activation and pore formation are associated with inflammation, particularly when induced by the inflammatory protease caspase-1 upon inflammasome activation. These gasdermin pores allow the release of the proinflammatory cytokines interleukin(IL)-1β and IL-18 and induce a lytic type of cell death, termed pyroptosis that supports inflammation, immunity, and tissue repair.However, even at the cellular level, the consequences of gasdermin activation are diverse and range from induction of programmed cell death -pyroptosis or apoptosis -to poorly characterized protective mechanisms. The specific effects of gasdermin activation can vary between species, cell types, the membrane that is being permeabilized (plasma membrane, mitochondrial membrane, etc.), and the overall biological state of the local tissue/cells. In epithelia, gasdermins seem to play crucial roles. Keratinocytes represent the main cell type of the epidermis, which is the outermost skin layer with an essential barrier function. Compared to other tissues, keratinocytes express all members of the gasdermin family, in part in a differentiationspecific manner. That raises questions regarding the specific roles of individual GSDM